Sugar beet pulp: Resurgence and trailblazing journey towards a circular bioeconomy. (15th March 2022) - Rana, Ashvinder K.; Gupta, Vijai Kumar; Newbold, John; Roberts, Dave; Rees, Robert M.; Krishnamurthy, Satheesh; Thakur, Vijay Kumar
Graphical abstract: Highlights: A complete review on utilization of sugar beet pulp in multi technologies. Extraction of bio-chemicals from sugar beet pulp. Chemical composition, thermal stability and crystallinity of sugar beet pulp. Role in the development of polymer composites and in water purification. Extraction of cellulose nano fibers and silica nano particles from pulp. Abstract: The present review article will outline alternative uses of sugar beet pulp residue produced during the preparation of sugar from sugar beet. Traditionally, sugar beet pulp has been used as cattle fodder and was not considered to have much potential to be utilised in other competitive industries such as bio-energy, polymer composites, water purification industries, etc. However, with technological advancement, sugar beet pulps have been successfully employed to reinforce polymer composites, extract nano elements, and bio-adsorb contaminants from wastewater or as precursor molecules to create various bio-chemicals. As per the data from the Food and Agriculture Association of United States (FAAU, 2019), the e sugar beet production is very much lower (85.71% approx.) compared to sugar cane. However, in near future, because of increasing demands of sugar from the growing world population and also due to shortage of freshwater resources, we may anticipate bulk production of sugar beet (which requires less freshwater resources than cane sugar and whose production as per FAAU data has increased inconsistently about 1.74% approx. in last five years, in tropical regions more specifically in European countries (currently share about 69.6% of total world sugar beet production) or in other parts of the world and thus it may lead to overproduction of sugar beet pulp. Therefore, it is the need for time and efforts made by different scientists to develop new chemical technologies t can consume waste sugar beet pulps residue for the generation of different beneficial products. The promising strategies for producing multifunctional materials from sugar beet pulp include pyrolysis, enzymatic/acid hydrolysis, surface functionalization, nanofibres extraction, stacking them as reinforcing agents in polymer composites and carbonization. The technologies evaluated in the present article will be of great interest to both scientists and industrialists.